Impact of Reduction in Drinking vs. complete Cessation on the Severity and Type of Alcohol-Related Problems in Women Living with HIV. (18th February 2021) - Richards, Veronica L.; Zhou, Zhi; Wang, Yan; Vaddiparti, Krishna; Brumback, Babette; Cook, Robert L.
Abstract: Background: Women living with HIV (WLWH) often report heavy alcohol use and may experience substantial alcohol-related problems, but it is unclear whether it is necessary to completely quit drinking to reduce such problems Objectives: To assess whether complete reduction of alcohol use produced significantly greater improvement in alcohol-related problems than a partial reduction of alcohol use (reducing alcohol use to ≤7 or ≤14 drinks per week). Methods: We used data from a randomized clinical trial examining the effectiveness of Naltrexone in WLWH who reported heavy drinking (>7 drinks/week) at baseline. The primary outcome (alcohol-related problems) was measured using the Short Inventory of Problems. The primary predictor (drinking status: quit drinking, reduced drinking, continue heavy drinking) was measured using a 30-day timeline followback. Results: The sample consisted of 163 WLWH (50% 50 years or older, 85% Black). WLWH who reported past violence had significantly greater mean SIP scores at baseline (19.9 vs. 10.5, p <.0001). Forty-eight percent of women quit drinking by 7 months and 28% reduced drinking to ≤7 drinks/week; these women had significant reduction in alcohol-related problems compared to those who continued heavy drinking (–8.2 and −4.8 vs. −0.8, p  = 0.0003). Quitting and reducing drinking were also associated with statistically significant decreases among the physical, interpersonal, intrapersonal, and social subscales of the SIP ( p <.05), although a similar pattern, while not statistically significant, exists for the impulse control subscale. Conclusions: While completely quitting drinking produced the greatest improvement, reducing drinking to ≤14 drinks per week can significantly reduce alcohol-related problems in WLWH.